Carotid artery disease: clinical features and management. Issue 6 (June 2018) - Naylor, A. Ross
Abstract: The most common single cause of ischaemic carotid territory stroke is thromboembolism from stenoses in the extracranial internal carotid artery (ICA). In the majority, embolism is preceded by an acute change in plaque morphology predisposing the patient to overlying thrombus formation and embolization. The management of patients with carotid artery disease mandates risk factor modification, antiplatelet and statin therapy in everyone. There is grade A, level I evidence that recently symptomatic patients with 50–99% NASCET stenoses gain significant benefit from carotid endarterectomy (CEA), despite a small risk of perioperative stroke. Maximum benefit is conferred if the patient undergoes surgery as soon as possible after onset of symptoms. The management of patients with asymptomatic disease remains controversial. The 2018 European Society for Vascular Surgery (ESVS) carotid guidelines now advise that asymptomatic patients with a 60–99% stenosis who have one or more clinical/imaging features that might make them at higher risk for stroke on medical therapy should be considered for CEA, with the remainder being treated medically. The 2018 ESVS carotid guidelines also advise that carotid artery stenting may be an alternative to CEA in 'average risk' symptomatic and asymptomatic patients, although CEA is still the preferred option when treating patients within 14 days of symptom onset.